The agricultural value chain between small or informal farmers and larger actors, whether the state or corporations. How is the C-19 crisis response to food supply shaping value chains? - Rapson, Mandy (Graduate School of Business (GSB), 2024)
Despite the attention placed on improving small-scale farmer resilience and sustainability in the face of climate change, very little is understood about how small-scale farmers respond during abrupt disruptions. To build resilience in small-scale farmers, decision-makers tend to invest in physical assets and in improving preparedness, reducing vulnerabilities, and implementing resilience-enhancing upgrades. However, evidence from disaster literature presents social capital, and disaster entrepreneurs and spontaneous ventures, as critical to community recovery. Therefore, this study explores the role of these types of ventures and their intermediary role for small-scale farmers during a crisis. It also describes how they use social capital to promote small-scale farmer resilience. The Covid-19 pandemic caused a dual crisis to supply chains by disrupting both the supply and demand of food. Government regulations reflected a continual undervaluing of the informal sector and exposed just how fragile small-scale farmer supply chains are. A longitudinal qualitative study was conducted between April 2020 and March 2022 on smallscale farmers from three diverse socio-geographic regions in three provinces in South Africa. The results showed that intermediaries were critical to the recovery of small-scale farmers. Spontaneous ventures acted as intermediaries and existing intermediaries adapted to respond to the critical needs of farmers in the crisis. Intermediaries worked together to create new pathways for food to flow by constructing alternative supply chains. A key argument is that there are two distinct kinds of intermediation that have, and make use of, the type of social capital that is available to them. These are labelled ‘bridging' and ‘bonding' intermediaries. It is impossible for a single intermediary to fulfil both roles, especially in contexts such as South Africa with dual economies. The research thus asserts that two kinds of intermediaries are required in order to connect these two distinct but complementary competencies and relationships. This knowledge is important for disaster managers, corporations and international development organisations focussed on developing small-scale farmer resilience, especially in abrupt crises but also for more gradual disruptions, such as climate change.